2015
DOI: 10.1007/s40333-015-0126-9
|View full text |Cite
|
Sign up to set email alerts
|

Blown sand motion within the sand-control system in the southern section of the Taklimakan Desert Highway

Abstract: Although scientists have performed many studies in the Taklimakan Desert, few of them have reported the blown sand motion along the southern edge of the Taklimakan Desert Highway, which differs significantly from the northern region in terms of aeolian sand geomorphology and formation environment. Based on the field observation data of airflow and aeolian sand transport, continuous monitoring data of erosional and depositional processes between 14 April 2009 and 9 April 2011 and data of surface sand grains fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In the field test, the structure of the wind-blown sand flux shows that the sand flux activity concentrates mainly near the surface in the 0-20 cm layer, which is consistent with the results of Cheng et al (2015). Because of the difference in scale, the characteristics of the wind-blown sand flux in the wind tunnel test differ from those observed in the field test.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the field test, the structure of the wind-blown sand flux shows that the sand flux activity concentrates mainly near the surface in the 0-20 cm layer, which is consistent with the results of Cheng et al (2015). Because of the difference in scale, the characteristics of the wind-blown sand flux in the wind tunnel test differ from those observed in the field test.…”
Section: Discussionsupporting
confidence: 84%
“…The W-beam central guardrails are commonly used on desert expressways to contribute to vehicle safety (Jason et al, 2005). In recent years, the deposition of the wind-blown sand on the subgrade surface with the W-beam central guardrails has become a concern (Li et al, 2016) because sand-blown erosion and sand deposition are the primary sources of sand damage on desert expressways (Lei et al, 2008;Cheng et al, 2015). The height and slope of the subgrade affect the airflow, which correlates negatively with wind velocity, and eddy airflow forms leeward of the subgrade (Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that geomorphology plays an important role in prevention of sand movement. Previous studies found that the slope toe and center part of a sand dune mainly exhibited surface deposition, whereas the crest of a dune primarily experienced surface erosion (Wang and Lei, 1998;Cheng et al, 2015).…”
Section: Amount Of Sand Transferredmentioning
confidence: 96%
“…These practices can effectively reduce wind erosion hazards. It has been demonstrated in the Taklimakan Desert that wheat straw used in checkerboard (straw-check) sand barriers may lower wind speeds by 33-90% and the sand transport rates by 60% (Cheng et al, 2015;Tian, Wu, Zhang, Lu, & Wang, 2015). The erosive resistance of gravel mulch is related to its coverage, pebble size, and spreading methods (Yuan, Lei, Mao, Liu, & Wu, 2009).…”
mentioning
confidence: 99%